Review of Autism Profiles and Response to Sertraline in Fragile X Syndrome-Associated Autism vs. Non-syndromic Autism; Next Steps for Targeted Treatment - Rajaratnam, Akash; Potter, Laura Axelrod; Biag, Hazel Maridith Barlahan; Schneider, Andrea; Petrasic, Ignacio Cortina; Hagerman, Randi Jenssen (Frontiers in Neurology, 2020)
Given significant genetic, molecular, and phenotypic overlaps, researchers have begun to investigate whether targeted treatments for Fragile X Syndrome (FXS) could also be beneficial for patients with Autism Spectrum Disorder (ASD). For example, low-dose sertraline, an SSRI, was used in two recent controlled trials in children with FXS and ASD. The first trial recruited 52 children with FXS, 32 of which were also diagnosed with ASD; the second trial recruited 58 children with non-syndromic ASD. One focus of the present study is to compare the response to sertraline between the FXS-associated ASD and non-syndromic ASD groups. Another focus is to compare baseline ASD-related characteristics between the groups and review these differences within the context of recent literature comparing these populations. Our comparison showed more severe ASD profiles in children with non-syndromic ASD versus FXS-associated ASD. Regarding response to sertraline, the FXS-ASD group displayed significant improvements in language development, while the non-syndromic group did not show any significant improvements. One possible explanation for this differential response is the distinct anxiety profiles that are seen in these two groups. The heightened anxiety phenotype seen in those with FXS-ASD may have led to a greater relief of anxiety symptoms with sertraline compared to those with non-syndromic ASD; this, in turn, could have led to measurably greater developmental gains. Further research is required to solidify this connection between anxiety relief and developmental gains in these populations.